Comparative Study of Janumet and Metformin in Glycemic Control among Patients with Type 2 Diabetes Mellitus - Mohamed, Amal (AlQalam Journal of Medical and Applied Sciences, 2026)
This study compares the clinical efficacy of Janumet versus Metformin in improving blood sugar control in patients with Type 2 Diabetes Mellitus, focusing on physiological differences between the sexes. The study sample consisted of 160 patients, divided equally into two treatment groups of 80 patients each. The study methodology included measuring random blood sugar levels (RBS), fasting blood sugar (FBS), and glycated haemoglobin (HbA1c) before and after the therapeutic intervention. This was done by reviewing medical records (pre- and post-treatment analyses). Statistical analysis of the data was performed using t-tests for differences and one-way analysis of variance (ANOVA). The results indicate statistically significant improvements in patients using Janumet, reducing all measured blood sugar parameters (p < 0.001), with a mean HbA1c reduction of 1.8375. Similarly, Metformin also showed statistically significant reductions across all parameters (p < 0.001), with a mean HbA1c reduction of 0.7625. Comparative analysis revealed Janumet demonstrated significantly greater reductions in RBS, HbA1c, and FBS compared to Metformin (all p < 0.001). The analysis also revealed statistically significant differences in the rate of improvement attributable to gender. In the Janumet group, males showed a clear reduction in FBS (1.9210) while females exhibited greater improvement in RBS levels (1.0238), both with p < 0.001. Furthermore, HbA1c in the Janumet group also showed statistically significant gender-related differences (p < 0.05). In the Metformin group, males demonstrated superior improvement in RBS levels (0.3529) compared to females (0.1956), with p < 0.001. Statistically significant gender-based differences were also identified for HbA1c and FBS in the Metformin group (both p < 0.05). Overall, this study suggests that combination therapy offers a synergistic advantage over monotherapy and highlights the importance of incorporating individual patient characteristics, most notably gender, into the design of a treatment regimen to achieve optimal results.